MENGGAGAS KONSEP DAN MODEL IDEAL PERLINDUNGAN HUKUM TERHADAP WHISTLEBLOWER DAN JUSTICE COLLABORATOR DALAM UPAYA PENANGGULANGAN ORGANIZED CRIME DI INDONESIA MASA MENDATANG - Lilik Mulyadi (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2014)
Practice of whistleblower and justice collaborator law protection especially in the effort to destroy the organized crime in Holland, germany and Australia to institution and the protect orientation is variatif and partial. Protection practice in Holland uses witness agreements, it is the agreement between the public prosecutor and witness to give the testimony with reward especially to organized crime. In Germany, trough Witness Protection Law In Process Criminal Investigation and Protection Against Victims (Zeugenschutzgesetz/ZschG). Essentially, Zeugenschutzgesetz/ZschG rules the dimention for the witnesses, both witnesses and not the victims. Besides, it is also ruled about rights issues witnesses before the trial and during the trial process. On the aspect of witness rights before the trial include the examination of witnesses in the policemen and prosecution, the secret of witness identity and the changes of witness identity. Then, the witness right in the trial are separated examination of the suspect and inspection with a camera recording. Then in Australia trough the National witness Protection Program with a secret identity, no responsibility in criminal and civil, the protection from the defamation, the protection from criminal acts of retaliation and conditionalprotection if their names are published to the media.Keywords: Law Protection, whistleblower, justice collaborator and organized crime